2008
DOI: 10.1080/15419060802014370
|View full text |Cite
|
Sign up to set email alerts
|

The Second PDZ Domain of Zonula Occludens-1 Is Dispensable for Targeting to Connexin43 Gap Junctions

Abstract: Zonula occludens (ZO)-1 is emerging as a central player in the control of gap junction (GJ) dynamics. Previously the authors reported that ZO-1 localizes preferentially to the periphery of Cx43 GJs. How ZO-1 arrives at GJ edges is unknown, but this targeting might involve we established interaction between the Cx43 C-terminus and the PDZ2 domain of ZO-1. Here the show that despite blocking the canonical PDZ2-mediated interaction by fusion of GFP to the C-terminus of Cx43, ZO-1 continued to target to domains ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…4a). As has been previously described, ZO-1 localized to the GJ edge and surrounding area (Hunter et al 2005; Hunter and Gourdie 2008; Palatinus et al 2011; Zhu et al 2005). In a result confirming that described by Yoram Rudy and coworkers (Kucera et al 2002), we found a high degree of overlap between the Cx43 and Na v 1.5 signals (Fig.…”
Section: Resultssupporting
confidence: 61%
“…4a). As has been previously described, ZO-1 localized to the GJ edge and surrounding area (Hunter et al 2005; Hunter and Gourdie 2008; Palatinus et al 2011; Zhu et al 2005). In a result confirming that described by Yoram Rudy and coworkers (Kucera et al 2002), we found a high degree of overlap between the Cx43 and Na v 1.5 signals (Fig.…”
Section: Resultssupporting
confidence: 61%
“…10), and by our findings demonstrating the failure of Cx43-EYFP, Cx43⌬363, Cx43⌬257, and Cx43⌬257-EYFP (which do not bind ZO-1) to assemble into GJs. This line of thought is further supported by the studies, which showed that the specific interaction between the PDZ2 domain of ZO-1 and Cx43 was required for GJ assembly but not for trafficking to the cell surface (56,57). Our data also support the conclusions drawn from earlier studies, which showed that the clustering of cell-cell channels to form nascent GJ puncta and their incorporation into the plaques, but not the maintenance of matured GJ plaques, was dependent on an intact actin cytoskeleton (58 -60).…”
Section: Discussionsupporting
confidence: 60%
“…How ZO-1 is incorporated into the borders of the gap junctional plaque is not fully understood. However, it has been shown previously that ZO-1 can be localized to gap junctional border zones using a mechanism independent from its direct binding to the C-terminal residues in Cx43 (Hunter and Gourdie, 2008). Given that our current data shows that Vcl and ZO-1 directly interact, we suggest that Vcl might function as a linker anchoring ZO-1 to gap junctions, the actin cytoskeleton and even other common binding partners such as F-actin, a-actinin, and a-catenin.…”
Section: Discussionmentioning
confidence: 99%